2005
DOI: 10.1111/j.1462-2920.2005.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity, osmotic stress and degradation of pesticide mixtures in soil extract liquid broth inoculated withPhanerochaete chrysosporiumandTrametes versicolor

Abstract: In this study we examined the extracellular enzymatic activity of two white rot fungi (Phanerochaete chrysosporium and Trametes versicolor) in a soil extract broth in relation to differential degradation of a mixture of different concentrations (0-30 p.p.m.) of simazine, dieldrin and trifluralin under different osmotic stress (-0.7 and -2.8 MPa) and quantified enzyme production, relevant to P and N release (phosphomonoesterase, protease), carbon cycling (beta-glucosidase, cellulase) and laccase activity, invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 35 publications
(29 reference statements)
1
31
0
Order By: Relevance
“…There are reports about simazine biodegradation by strains of algae [15], bacteria [12,40], yeasts [35], fungi [14,24], or mixed microbial communities [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are reports about simazine biodegradation by strains of algae [15], bacteria [12,40], yeasts [35], fungi [14,24], or mixed microbial communities [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Siddique et al [31] reported that Pandoreae species shown the highest degradation of α-and γ-HCH (67.1 and 60.2%, respectively) at an initial pH of 8 in liquid medium. In previous studies, Fragoeiro and Magan [38] observed that two white rot fungi, Phanerochaete chrysosporium and Trametes versicolor, had the ability to degrade different groups of pesticides (simazine, dieldrin and trifluralin) in a nutritionally poor soil extract broth.…”
Section: Growth Of Streptomyces Sp M7 In Soil Extractmentioning
confidence: 99%
“…A thermophilic Bacillus degraded 2-trifluoromethylphenol yielding the same fluorometabolite (Reinscheid et al 1998). The degradation of pesticides and herbicides that contain the trifluoromethyl group has been investigated in algae (Zablotowicz et al 1998), fungi (Guha et al 1995;Fragoeiro and Magan 2005), and bacteria (Bellinaso et al 2003), which co-metabolise the compounds without loss of fluorine.…”
Section: Biotransformation Of Organofluorine Compoundsmentioning
confidence: 99%